A Novel Metric for Hospital Quality in Kidney Cancer Surgery: A Veterans Affairs National Health System Validation of Concept. Issue 3 (29th May 2022) - Aguilar Palacios, Diego; Wilson, Brigid; Michael, Patrick; Saarela, Olli; Ascha, Mustafa; Song, Sunah; DeWitt-Foy, Molly E.; Lawson, Keith; Barnholtz-Sloan, Jill; Finelli, Antonio; Campbell, Steven C.; Abouassaly, Robert
Abstract: Introduction: We aimed to develop and validate a Compound Quality Score (CQS) as a metric for hospital-level quality of surgical care in kidney cancer at the Veterans Affairs National Health System. Methods: A retrospective review of 8, 965 patients with kidney cancer treated at Veterans Affairs (2005–2015) was performed. Two previously validated process quality indicators (QIs) were explored: the proportion of patients with 1) T1a tumors undergoing partial nephrectomy and 2) T1-T2 tumors undergoing minimally invasive radical nephrectomy. Demographics/comorbidity/tumor characteristics/treatment year were used for case mix adjustments at hospital level. The predicted versus observed ratio of cases was calculated per hospital to generate QI scores using indirect standardization and multivariable regression models. CQS represents the sum of both scores. A total of 96 hospitals were grouped by CQS, and short-term patient-level outcomes were regressed on CQS levels to assess for length of stay (LOS), 30-day complications/readmission, 90-day mortality and total cost of surgical admission. Results: CQS identified 25/33/38 hospitals with higher/lower/average performance, respectively. High performance hospitals had higher nephrectomy volumes (p <0.01). Total CQS independently associated with LOS (β=−0.04, p <0.01, predicted LOS 0.84 days shorter for CQS=2 versus CQS=−2), 30-day surgical complications (OR=0.88, p <0.01) or 30-day medical complications (OR=0.93, p <0.01) and total cost of surgical admission (β =−0.014, p <0.01, predicted 12% lower cost for CQS=2 versus CQS=−2). No association was found between CQS and 30-day readmissions or 90-day mortality (all p >0.05), although low event rates were observed (8.9% and 1.7%, respectively). Conclusions: Variability in quality of surgical care at hospital level can be captured with the CQS among patients with kidney cancer. CQS is associated with relevant short-term perioperative outcomes and surgical cost. QIs should be used to identify, audit and implement quality improvement strategies across health systems.